Business information systems : 18th International Conference, BIS 2015, Poznań, Poland, June 24-26, 2015, Proceedings /: 18th International Conference, BIS 2015, Poznań, Poland, June 24-26, 2015, Proceedings. (2015) - Unknown
No abstract available